LAPORAN ARUS KAS, PRODUKTIVITAS KARYAWAN PADA KINERJA PERUSAHAAN : BUKTI DARI PERUSAHAAN FOOD AND BEVERAGE - Mishelei Loen, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
This study aims to examine the effect of Cash Flow Reports and Employee Productivity on the Performance of Food and Beverage Companies Listed on the Indonesia Stock Exchange in 2019 – 2022. The data used in this research is quantitative data. The sampling technique used purposive sampling obtained a total number of samples. 76 data. Data collection with documentation and data processing with t test, f test, and test the coefficient of determination of multiple linear regression using the classical assumption test. The results of the study show that the Cash Flow Report as measured by Operating Cash Flow (AKO) has a positive and significant effect on company performance; Employee productivity as measured by Revenue Per Employee (RPE) has a positive and significant effect on company performance; Statements of Cash Flow as measured by Operating Cash Flow (AKO) and Employee Productivity as measured by Revenue Per Employee (RPE) have a positive and significant effect on company performance. As for suggestions related to this research, companies listed on the Indonesia Stock Exchange should improve company performance to increase company value. This will affect the profit that will be generated. The better the company's performance will make investors interested in investing or investing in the company.